The relationship between teachers' perception on instructional supervision and principal trust / Nur Amira Aisyah Sabarudin - Sabarudin, Nur Amira Aisyah (2014)
The purpose of this study was to identify the relationship between teachers' perception of instructional supervision and principal trust in secondary schools in Selangor. Four secondary schools from Petaling Perdana district were selected for the study. Data were collected using questionnaire. The questionnaire was distributed to a total of 300 randomly selected teacher respondents. However, only 208 questionnaires had been returned and were able to be used for analysis. Data were analysed using descriptive and inferential statistics. The findings revealed that the level of five dimensions of instructional supervision namely purpose, collaboration, continuity, feedback and instructional improvement were at high level. Among these dimensions, purpose was identified as the highest mean score. In addition, findings indicated that professional growth plan was the most frequent model being applied by principals. The findings also indicated that the level of principal trust was at high level. There was a strong and significant relationship between instructional supervision and principal trust. Implications for practice suggest how principals as instructional supervisor have a duty to supervise and monitor instruction regularly. In addition, this study has implications to the role of principal and teachers to enhance the process of instructional supervision, thereby producing successful schools. Based on the findings, this study also provides recommendations for improvement of practices and future research.